Re-Inventing the Fight against High Maternal Mortality among Developing Nations: A Case Study of Nigeria - Mercy Okeke, Nkechi; Mbagwu Okeke, Polycarp; Ngozi, F. Nnaji (International Journal of Psychosocial Rehabilitation, 2021)
This study aimed to determine the strategies for re-inventing the fight against high maternal mortality among developing nations using Nigeria as a case study. Specifically, the study ascertained the preventive measures for maternal mortality among pregnant women in rural communities in Nsukka local government area of Enugu State, Nigeria. One research question was used to identify the preventive measures of maternal mortality among these women in Nsukka local government area of Enugu State, Nigeria. The survey design was used. Data was collected using a questionnaire. A total of 108 pregnant women participated in the study. Data were analyzed using mean and standard deviation. The study revealed that administering test, management of pre-eclampsia, anemia, tetanus toxoid, screening infection, prompt treatment and magnesium sulfate using skilled care at delivery, a cesarean section in case of prolonged labour, family planning counselling, and use of essential vaccinations are noted for preventing maternal mortality. Based on the study, the following recommendations are made: education of women to raise their decision-making power, government and NonGovernmental Organizations should offer financial support to families to cushion the effect of maternal death, the government should establish legal law with a penalty to abolish harmful practices like FGM and child marriage below 18 years, the government should implement the full practice of Safe Motherhood in all the rural poor and government should make child and maternal survival a core national and global health concern